Nutritional interventions to support acute mTBI recovery - Finnegan, Emma; Daly, Ed; Pearce, Alan J.; Ryan, Lisa (Frontiers in Nutrition, 2022)
When mild traumatic brain injury (mTBI) occurs following an impact on the head or body, the brain is disrupted leading to a series of metabolic events that may alter the brain’s ability to function and repair itself. These changes may place increased nutritional demands on the body. Little is known on whether nutritional interventions are safe for patients to implement post mTBI and whether they may improve recovery outcomes. To address this knowledge gap, we conducted a systematic review to determine what nutritional interventions have been prescribed to humans diagnosed with mTBI during its acute period (< 14 days) to support, facilitate, and result in measured recovery outcomes. Methods: Databases CINAHL, PubMed, SPORTDiscus, Web of Science, and the Cochrane Library were searched from inception until January 6, 2021; 4,848 studies were identified. After removing duplicates and applying the inclusion and exclusion criteria, this systematic review included eleven full papers. Results: Firstly, patients' that received calorie and macronutrient (protein) intakes tailored to their injury severity, and sex within 96 hours post mTBI had a reduced length of stay in hospital. In addition, patients receiving acute nutrients and non-nutrient support within 24-96 hours demonstrated positive recovery outcomes post mTBI. Interventions that included omega-3s (DHA and EPA), vitamin D, mineral magnesium oxide, amino acid N-acetyl cysteine, hyperosmolar sodium lactate, and nootropic Cerebrolysin, all demonstrated positive recovery outcomes; such as symptom resolution, improved cognitive function and resolved present nutrient deficiencies for patients post mTBI. Conclusion: Our findings suggest that nutrition plays a positive role during acute mTBI recovery. Following mTBI, patient needs are unique, and this review presents the potential for certain nutritional therapies to support the brain in recovery, specifically omega-3 fatty acids. However, due to the heterogenicity nature of the studies available at present it is not possible to make definitive recommendations.